How the end of armed conflicts influence forest cover and subsequently ecosystem services provision? An analysis of four case studies in biodiversity hotspots. (February 2019) - Grima, Nelson; Singh, Simron J.
Highlights: Ecosystem Services provision is, in part, closely linked to biodiversity and forest cover. We analyse forest cover data for 4 countries that experience armed conflicts in the last 20 years. The results show alarming forest loss right after armed conflicts end. We propose adaptive co-management to address governance challenges during the transition period. Abstract: Ecosystem Services are commonly understood as the goods and services people obtain from nature, such as carbon sequestration, provision of food and fibres, pollination, etc. The provision of these services is in part closely related to the level of biodiversity in a region. Since some forested regions are considered biodiversity hotspots, the loss of such forested areas would affect the provision of ecosystem services. Among others, expansion of the agricultural frontier, demand for timber, weak enforcement of environmental regulations, or illegal logging are some of the key factors contributing to forest loss. These factors can be supported or enhanced during or after periods of extreme social instability such as armed conflicts or wars. Analyzing forest cover data for four different countries that have experienced armed conflicts in the recent past (Nepal, Sri Lanka, Ivory Coast and Peru), we seek to understand the influence of armed conflicts in ecosystem services provision, aiming to identify social, political and institutional drivers. Our four case studies show that at the end of their armed conflicts, on an average there was a 68.08% increase of annual forest loss in the five years following the end of conflict, as compared to the worldwide 7.20% mean. We identified inappropriate governance and institutional arrangements as the key driver during the transition period. We argue that as part of a family of bottom-up approaches, the adaptiveco-management approach is a promising option to deal with similar situations in the future, helping to keep a sustainable provision of ecosystem services.